URGENSI PENGATURAN LENIENCY PROGRAM TERHADAP DUGAAN KARTEL ATAS KELANGKAAN MINYAK GORENG DI INDONESIA - Putra Rizal Pratama, Arya; Setyawati, Ria; Budi Kagramanto, L.; Aju Wulandari, Sinar (UNES Law Review, 2023)
Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition stipulates various prohibitions for actions that cause unfair business competition, especially contractual activities between business actors, one of which is a cartel The actions of this cartel have an impact on the sustainability and welfare of consumers as a result of price and production regulation in the market. In proving the realm of unfair business competition, namely cartel, it can be proven through indirect evidence. Indirect evidence according to the Regulation of the Commission for the Supervision of Business Competition Number 1 of 2010 concerning Procedures for Handling Cases is a guide. The cartel case approach which is regulated through Article 11 of Law Number 5 of 1999 adopts the principlerule of reason tend to see and examine the reasons of business actors who commit an act that is considered to violate the competition law. However, the success of disclosing cartel cases is still experiencing obstacles. Several countries have implemented leniency program as a response to cartel cases. The process of enforcing business competition law in Indonesia has not been able to overcome cartel cases that have harmed consumers. The results of this study explain the difficulty in disclosing cartel cases in Indonesia because there are no parties or informants to assist law enforcement to ascertain the alleged cartel. The urgency of the leniency program is the only way to reduce difficulties and restore an efficient and effective economic situation so that consumers are able to prosper.